Bacterial Contamination of Stethoscope Chest Pieces and the Effect of Daily Cleaning. (20th February 2013) - Fujita, H.; Hansen, B.; Hanel, R.
<x xml:space="preserve">Abstract</x> Background Stethoscopes are a potential source of nosocomial infection for hospitalized humans, a phenomenon not previously studied in companion animals. Objectives To determine if daily cleaning of stethoscope chest pieces reduces bacterial contamination between cleanings. Animals Client‐owned dogs and cats. Methods Prospective observational study. In phase 1, bacterial cultures were obtained from the chest pieces of 10 participant stethoscopes once weekly for 3 weeks. In phase 2, stethoscopes were cleaned daily and 2 culture samples were obtained once weekly, immediately before and after cleaning with 70% isopropyl alcohol, for 3 weeks. Results Daily cleaning eliminated bacteria immediately after each cleaning (P = .004), but did not reduce the rate of positive cultures obtained before cleaning in phase 2. Cultures were positive for 20/30 (67%) samples during phase 1 and 18/30 (60%) obtained before daily cleaning during phase 2. Recovered organisms included normal skin flora, agents of opportunistic infections, and potential pathogens. The only genus that was repeatedly recovered from the same stethoscope for 2 or more consecutive weeks was Bacillus sp. Conclusions and Clinical Importance Daily cleaning was highly effective at removing bacteria, but provided no reduction in precleaning contamination. Cleaning stethoscopes after use on dogs or cats infected with pathogenic bacteria and before use on immunocompromised animals should be considered.